ASSESSMENT OF NUTRITIONAL STATUS IN CHILDREN FROM 0 TO 5 YEARS OF AGE FROM LARA STATE (Boletin Médico de Postgrado, 2024)
In order to assess the nutritional status in a group of children under 5 years of age, a non-experimental quantitative descriptive study was carried out, with non-probabilistic intentional sampling in children with an age range of 0 to 5 years old. The nutritional status was evaluated with a scale calibrated with a height meter and with a Health brand infantometer, in 3795 children of both sexes who were attended at Health Days held in various municipalities of the state of Lara and the results of anthropometric indicators obtained and analyzed with descriptive statistics showed that 598 children were underweight, 263 children had acute malnutrition and 1143 had chronic malnutrition.